Preparation and evaluation of carriers for detection of cholinesterase inhibitors - Vetchý, David; Pitschmann, Vladimír; Vetchá, Martina; Kašparovský, Tomáš; Matějovský, Lukáš (Neuro-endocrinology letters, 2015)
OBJECTIVES: The aim of the study was to use methods of pharmaceutical technology, and prepare carriers in the form of pellets suitable as a filling of detection tubes for enzymatic detection of cholinesterase inhibitors. The enzymatic detection was based on enzymatic hydrolysis of acetylthiocholine iodide and the subsequent colour reaction of its hydrolysis product with Ellman's reagent. The suitable carriers should be in the form of white, regular and sufficiently mechanically resistant particles of about 1 mm allowing it to capture the enzyme during the impregnation process and ensuring its high activity for enzymatic detection. METHODS: Carriers consisting of microcrystalline cellulose, lactose, povidone, and sodium carboxymethyl cellulose were prepared using extrusion-spheronization method under three different drying conditions in either a hot air oven or a microwave oven. Subsequently, the carriers were impregnated with acetylcholinesterase and their size, shape, mechanical resistance, bulk, tapped and pycnometric density, Hausner ratio, intraparticular and total tapped porosity, and activity were measured and recorded. RESULTS: In this procedure, carriers with different physical parameters and different acetylcholinesterase activity were evaluated. It was found that higher acetylcholinesterase activity was associated not only with a higher intraparticular porosity but also with more regular particles characterized by high sphericity and low total tapped porosity. CONCLUSION: This unique finding is important for the preparation of detection tubes based on enzymatic detection which is still irreplaceable especially in the field of detection and analysis of super-toxic cholinesterase inhibitors.
Keywords: sodná sůl karboxymethylcelulosy; acetylthiocholin; Lactose; poréznost; celulosa; testování materiálů; sulfhydrylová reagencia; Carboxymethylcellulose Sodium; Sulfhydryl Reagents; Povidone; cholinesterasové inhibitory; laktosa; Cellulose; povidon; Dithionitrobenzoic Acid; Porosity; kyselina dithionitrobenzoová; Acetylthiocholine; Cholinesterase Inhibitors; Materials Testing